Calculation of Protection Function Settings of New Elements of the 500 kV Transmission System - Sučević, Nikola J. (Proceedings, Electrical engineering institute "Nikola Tesla", 2022)
In the paper the protection function setting calculations for elements of the transmission system are shown. Analyzed transmission system consists of the 500 kV and 230 kV voltage levels. The setting calculations are shown for several protection functions for the 500 kV reactors, 500/230 kV/kV autotransformers and 500 kV line. Network modeling and analysis have been performed using DIgSILENT PowerFactory.
Keywords: transmission system; protection function settings; software simulations